2001
DOI: 10.1677/joe.0.1690417
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis and necrosis by zinc in human thyroid cancer cell lines

Abstract: Zinc at concentrations of 150 µM or higher induced necrosis as well as apoptosis in thyroid cancer cell lines. Necrosis was induced by zinc in a dose-dependent manner, whereas apoptosis did not increase at higher concentrations of zinc. The expression of the antiapoptotic protein phosphorylated Bad was markedly increased, whereas the expression of the proapoptotic proteins Bax and Bad decreased following Zn 2+ exposure. Zn 2+ induced rapid degradation of I B, and an increase in the binding of nuclear transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 33 publications
0
11
0
1
Order By: Relevance
“…acquired from studies on the effects of zinc supplementation in zinc-deficiencies such as inflammatory bowel disease and others (3). On the other hand, it has been demonstrated that externally supplied zinc inhibits the growth and proliferation of several types of tumor cells, including colon cancer cells (5,7,11). Particularly interesting appears to be the ability of zinc to inhibit colon cancer cells proliferation via a direct effect on the cytoskeleton, in particular microtubules (6).…”
Section: Discussionmentioning
confidence: 99%
“…acquired from studies on the effects of zinc supplementation in zinc-deficiencies such as inflammatory bowel disease and others (3). On the other hand, it has been demonstrated that externally supplied zinc inhibits the growth and proliferation of several types of tumor cells, including colon cancer cells (5,7,11). Particularly interesting appears to be the ability of zinc to inhibit colon cancer cells proliferation via a direct effect on the cytoskeleton, in particular microtubules (6).…”
Section: Discussionmentioning
confidence: 99%
“…Many of those studies employed extremely high unphysiologic levels of zinc that would never occur in situ even under severe pathological conditions. However some studies have demonstrated that zinc induces apoptosis in selective cells (Provinciali et al, 1995;Hamatake, 2000;Iitaka et al, 2001;Haase et al, 2001;Jiang et al, 2001). In the case of prostate cells, two requirements are essential for the manifestation of zinc-induced apoptosis: the cells must possess the capability of accumulating high cellular levels of mobile reactive zinc; and the mitochondria of the cells must be directly responsive to zinc induction of cytochrome c release.…”
Section: Zinc Effects On Mitochondrial Apoptogenesismentioning
confidence: 99%
“…As a cofactor for an estimated 3,000 human proteins [17], aberrations in zinc homeostasis contribute to development and progression of human cancers [18, 19]. Previous studies are mainly focused on the cytotoxicity of excessive zinc supplement on cancer cells [20-22]. Recently, N, N, N', N'-tetrakis-(2-pyridylmethyl)-ethylene-diamine (TPEN), a membrane-permeable zinc chelator, shows pro-apoptotic effects on some cancer cells, indicating that zinc depletion may be a potential strategy for cancer treatment [23, 24].…”
Section: Introductionmentioning
confidence: 99%